Spatially Controlled Supramolecular Polymerization of Peptide Nanotubes by Microfluidics. (27th February 2020) - Méndez‐Ardoy, Alejandro; Bayón‐Fernández, Alfonso; Yu, Ziyi; Abell, Chris; Granja, Juan R.; Montenegro, Javier
Abstract: Despite the importance of spatially resolved self‐assembly for molecular machines, the spatial control of supramolecular polymerization with synthetic monomers had not been experimentally established. Now, a microfluidic‐regulated tandem process of supramolecular polymerization and droplet encapsulation is used to control the position of self‐assembled microfibrillar bundles of cyclic peptide nanotubes in water droplets. This method allows the precise preferential localization of fibers either at the interface or into the core of the droplets. UV absorbance, circular dichroism and fluorescence microscopy indicated that the microfluidic control of the stimuli (changes in pH or ionic strength) can be employed to adjust the packing degree and the spatial position of microfibrillar bundles of cyclic peptide nanotubes. Additionally, this spatially organized supramolecular polymerization of peptide nanotubes was applied in the assembly of highly ordered two‐dimensional droplet networks. Abstract : Der räumlich regulierte Aufbau von synthetischen supramolekularen Fasern wird durch Mikrofluidik gesteuert. Die Modulation chemischer Auslöser wie pH‐Wert oder Ionenstärke ermöglicht die räumliche Organisation der in Wassertröpfchen eingeschlossenen supramolekularen Fasern. 2D‐Suprastrukturen können durch die Steuerung der Organisation der Tröpfchen‐ und Fibrillaranordnung aufgebaut werden.